2014
DOI: 10.2196/jmir.3049
|View full text |Cite
|
Sign up to set email alerts
|

Baby Boomers’ Adoption of Consumer Health Technologies: Survey on Readiness and Barriers

Abstract: BackgroundAs they age, baby boomers (born 1946-1964) will have increasing medical needs and are likely to place large demand on health care resources. Consumer health technologies may help stem rising health care needs and costs by improving provider-to-patient communication, health monitoring, and information access and enabling self-care. Research has not explored the degree to which baby boomers are ready for, or are currently embracing, specific consumer health technologies This study explores how baby boo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
70
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(73 citation statements)
references
References 57 publications
2
70
0
1
Order By: Relevance
“…Older adults tend to use the internet for health purposes [42][43][44]. A national survey revealed that, among Baby Boomers, about half go online for some health related purpose [40], such as ordering prescriptions or obtaining health information.…”
Section: Internet and Emailmentioning
confidence: 99%
See 1 more Smart Citation
“…Older adults tend to use the internet for health purposes [42][43][44]. A national survey revealed that, among Baby Boomers, about half go online for some health related purpose [40], such as ordering prescriptions or obtaining health information.…”
Section: Internet and Emailmentioning
confidence: 99%
“…Previous experience with or exposure to technology is another factor affecting older adult engagement with technology. Many adults now 50 and older utilized computers as a part of their employment [42]. These individuals demonstrate a level of comfort with new technology, while others without such experience do not [52,81,82].…”
Section: Personal Factorsmentioning
confidence: 99%
“…In addition, more research is need to better understand how online social support is used by older adults and the challenges they may face in terms of accessing and using newer communication technologies. While researchers have examined online support and health-related technology for older adults (Wright, 2000a;LeRouge et al, 2014), more research and interventions are needed to design online support platforms and technologies for older adult populations. Qualitative research and quantitative studies can both make important contributions to the study of cultural influences on social support network and health outcome processes (as well as to the larger area of social support and health research).…”
Section: A Research Agenda For the Study Of Social Network Support Anmentioning
confidence: 99%
“…Son on yılda sessiz kuşakla ilgili olarak (Lehto, Jang, Achana, ve O'Leary, 2008;Strauss ve Howe, 1991) tarafından, Bebek Patlaması kuşağı ile ilgili ise (LeRouge, Van Slyke, Seale, ve Wright, 2014;Naidoo, Ramseook-Munhurrun, Seebaluck, ve Janvier, 2015;Nazarian, 2010;Yang ve Jolly, 2008) tarafından yapılan çalışmalar bunlardan bazılarıdır. Ancak Hariri'nin (Adams, 2016) de sözünü ettiği gibi insan yaşamındaki uzamanın artan bir ivmeyle devam ediyor olmasının yaşlı kuşakların önemini artırıyor olması da göz önünde bulundurulması gereken bir gerçektir.…”
Section: Kuşak Kavramı X Ve Y Kuşaklarıunclassified